ANALISIS MODEL ANTRIAN MULTIPLE CHANNEL MULTIPLE PHASE SERVICE DALAM PROSES PEMBUATAN KARTU MAHASISWA (KTM) PADA BANK BNI UNTAD - Usman, R; Jaya, A I; Lusiyanti, D (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2019)
The queue is a common situation that is common in our daily lives as consumers waited in front of the booth to get a turn to the service or service facilities. One example is the manufacture queue Student Identity Card (KTM) Tadulako in Bank BNI UNTAD. The purposes of this research is to analyze the characteristics of the making of queue Student Identity Card (KTM) Tadulako in Bank BNI of UNTAD. By calculating the probability were no queues (ð‘ƒ0 ),the average customer in the queue (ð¿ð‘Ž),the average customer in the system (ð¿ð‘  ),the average waiting time for customers in the queue (Wa ),the average time waiting for customers in the system (Wð‘  ). The results showed that the model type of queue that is used in the manufacture of Student Card (KTM) Tadulako in Bank BNI UNTAD is a model of multiple channels-multiple phase (M / M / S) with a Poisson arrival pattern distribution and exponential distribution service time. The analysis shows the performance characteristics of a queuing system manufacture KTM BANK BNI of UNTAD can be said to have been effective, because of the steady state in each stage. On Wednesday, the value of (ð‘ƒ0 ) at CS is 0,145 and the teller is 0.8879,for the value of (ð¿ð‘Ž) in CS is 1.8821 and the teller customer is a customer 0.0004 tothe value (ð¿ð‘  ) 3.4948is the customer, to the value of (Wa ) on CS is 33.5373 minutes and the teller was 0.0075 minutes, to the value of (Wð‘  ) is 74.1952 minutes. On Thursday, the value of (ð‘ƒ0 ) on CS was 0.121 and the teller is 0.8837,for the value of (ð¿ð‘Ž) in CS is 2.4998 and the teller customer is a customer 0.0005 tothe value (ð¿ð‘  ) 4.1918is the customer, to the value of (Wa ) on CS is 42.4061 minutes and the teller was 0.0081 minutes, to the value of (Wð‘  ) is 71.1808 minutes.Keywords : Exponential Distribution, Poisson Distribution, Queue Multi Phase